Impact of high-speed handpiece noise-induced dental anxiety on heart rate: analyzing experienced and non-experienced patients - a comparative study - Raahim Salman Abdul Ghaffar; Mahnoor Sheikh; Muneeza Kidwai; Anas Sanaullah; Mousab Salman; Anum Ilyas; Naseer Ahmed; Abhishek Lal (BMC, 2024)
Abstract Background Dental anxiety is very much common among the patients and could be due to different factors like the behavior of the dentist, past experiences, Needle phobia, or word of mouth from other patients. According to recent studies, a strong association between sound and anxiety has been found, so this observational study has been conducted to find out the link between the activation of anxiety with the sound of a handpiece between experienced patients, who have already gone through the dental treatments and non-experienced patients. Methods Total of 297 participants were part of this study. These participants were divided into 2 groups according to the experienced and non-experienced dental patients. The researcher first filled out the CORAH Dental Anxiety Scale (DAS) form to mark the anxiety level of the patients, and then noted the readings of the heart rate in 3 intervals which were before during, and after the treatment with the pulse oximeter. Later the data was analysed using the SPSS independent t-test. Results Results show that patients in group 1 who have gone through the dental treatment before were less anxious and had a lesser effect on their heart rate than the patient who were having the treatment for the first time who were in group 2. Another interesting factor was noticed that in both the groups female were found to be more anxious than male participants. Participants with younger age were found to be more anxious than older age patient in both groups Conclusions The sound of the handpiece can provoke anxiety in the patient, affecting the heart and increasing the heart rate. Participants who were experienced were found to be less anxious than the participants who were inexperienced.